2009
DOI: 10.3318/bioe.2009.109.1.53
|View full text |Cite
|
Sign up to set email alerts
|

LEAD POISONING IN MUTE SWANS (<i>CYGNUS OLOR</i>) IN IRELAND: RECENT CHANGES

Abstract: Studies over two decades have shown a marked trend towards a decrease in blood lead levels in the mute swan (Cygnus olor) in parts of Ireland. However, this study shows that a small percentage of some populations of mute swans in Co. Cork still have significantly elevated lead levels, causing some potentially sublethal effects to the health status of the swans. Overall, at both urban and rural sites the median blood lead levels in adults and cygnets of both sexes were below a threshold level of 1.21mmol l (1 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Mute swans are particular sensitive to lead exposure and may serve as sentinel species for toxicological contaminations in the environment (Degernes 2008 ). The studies have found many route of exposure to lead in this species (Perrins et al 2003 ; Bowen and Petrie 2006 ; Degernes 2008 ; O’Connell et al 2009 ; Turner and Hambling 2012 ). Lead toxicosis induced significant changes in the values of commonly measured hematologic parameters in waterfowl (Katavolos et al 2007 ).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mute swans are particular sensitive to lead exposure and may serve as sentinel species for toxicological contaminations in the environment (Degernes 2008 ). The studies have found many route of exposure to lead in this species (Perrins et al 2003 ; Bowen and Petrie 2006 ; Degernes 2008 ; O’Connell et al 2009 ; Turner and Hambling 2012 ). Lead toxicosis induced significant changes in the values of commonly measured hematologic parameters in waterfowl (Katavolos et al 2007 ).…”
Section: Introductionmentioning
confidence: 98%
“…Hematology may show hemolytic anemia (mild to moderate) with Heinz bodies, poikilocytosis, polychromasia. The increased serum uric acid concentrations, LDH and total protein could be observed (O’Halloran et al 1988 ; Campbell and Ellis 2007 ; Katavolos et al 2007 ; Degernes 2008 ; O’Connell et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One year after the supplementation, a decrease in Pb shot ingestion from 39.4% to 8.3% was observed in tufted ducks (Aythya fuligula) but not in common teal (Anas crecca) or mallards (Anas platyrhynchos; Hoffmann 1960). More recently, grit supplementation helped reduce mortality by Pb poisoning due to the ingestion of Pb weights in mute swans (Cypus olor) at Cork Lough (Ireland; O'Halloran et al 2002;O'Connell et al 2009). Experiments with captive mallards showed that grit availability reduced both Pb shot ingestion (Mateo and Guitart 2000) and the effects of Pb poisoning (Godin 1967;Longcore et al 1974).…”
Section: Communicated By C Gortázarmentioning
confidence: 99%
“…In this case, 40 tonnes of sandstone <10 mm was first spread in 1986, and 50 tonnes was added annually from 1997 to 2000 (O'Halloran et al 2002). Later in the same area, 150 tonnes of grit was supplemented from 2001to 2005(O'Connell et al 2009). After grit supplementation, declines in the median blood lead level and in the proportion of swans suffering from acute lead poisoning were observed (O'Halloran et al 2002;O'Connell et al 2009).…”
Section: Management Implicationsmentioning
confidence: 99%